Organic polymers as additives in enhancement of laminar liquid flow in microchannels - W.M. Ling, Fiona; J.T., Heng; Abdulbari, Hayder A. (Universiti Malaysia Pahang, 2018)
Drag reduction has been widely incorporated into various applications by introducing a minute amount of long chain flexible polymers into the core of the fluid flow in pipes, ducts and conduits. Recently, this technique started to gain attention of the researchers to be applied in medical field where the flow is mostly laminar. In this present work, three organic polymers as drag reducing additives were selected to test their flow enhancement performance in the micro-flow system connected to a 100 µm straight microchannel. The additives were extracted from three different plant sources namely, okra, aloe vera and hibiscus leaves using water extraction method. Characterization of additives such as rheology analysis was conducted.